Factors Affecting Purchasing Decisions at Nayla Buah (NB) Store Tebeng In Bengkulu City - Ayu Andri; Ida Anggriani; Nirta Vera Yustanti (Penerbit Jurnal Indonesia, 2021)
This study aims to determine the effect of cultural, social, personal, and psychological factors on purchasing decisions and to determine the effect of all the factors simultaneously on purchasing decisions at Nayla Buah (NB) storeTebeng, Bengkulu City. This research is an associative research, which conducted to determine the value of the independent variable, one variable or more than one variables, which aims to determine the relationship between the variables. The method used is a survey. The population in this study were 1200 consumers. The sample of respondents were 92 consumers. The validity using the Pearson Coefficient Correlation with a significance value of 5% with a critical value and the reliability test based on the Cronbach Alpha coefficient and hypothesis testing using multiple regression analysis. The results showed that (1) There is no significant influence of cultural factors on purchasing decisions at Nayla Buah Bengkulu City with a significance value greater than 0.05, namely 0.144. (2) There is a positive and significant influence of social factors on purchasing decisions at Nayla Buah store with a significance value smaller than 0.05, namely 0.013. (3) There is a positive and significant influence of personal factors on purchasing decisions at Nayla Buah store with a significance value smaller than 0.05, namely 0.030. (4) There is no significant effect of psychological factors on purchasing decisions at Nayla Buah store with a significance value greater than 0.05, namely 0.432. (5) There is a positive and significant influence of cultural, social, personal and psychological factors on purchasing decisions at Nayla Buah store with a significance value of 0.000 which is smaller than 0.05. (6) The factors that influence purchasing decisions are social and personal factors.